2022
DOI: 10.3390/healthcare10101907
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Stigma, Cognitive Appraisals, Coping Strategies and Stress Responses among Japanese Women Undergoing Infertility Treatment

Abstract: The number of infertility treatment cycles in Japan is the highest worldwide. Studies have shown that stigma is a predictor of stress-related symptoms including anxiety and depression in women undergoing infertility treatment. Stress management to prevent stress-related symptoms may be crucial; however, few studies have examined the model of stigma and stress responses. Based on the stress-coping model, we hypothesized that stigma threatens the identity of such women and that coping failure increases stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(111 reference statements)
1
4
0
Order By: Relevance
“…Similarly, high levels of stigma have also been reported in other studies (19)(20)(21). It has been well established in the literature that infertility stigma was associated with a wide range of negative health outcomes, including low self-esteem, low self-e ciency, failure in coping, and social isolation, which all contributed to high psychological distress such as depression and anxiety, and even suicide ideation (22)(23)(24)(25). In addition, infertile women with high stigma were less likely to seek treatment and more likely to discontinue treatment even if they sought treatment (26,27).…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, high levels of stigma have also been reported in other studies (19)(20)(21). It has been well established in the literature that infertility stigma was associated with a wide range of negative health outcomes, including low self-esteem, low self-e ciency, failure in coping, and social isolation, which all contributed to high psychological distress such as depression and anxiety, and even suicide ideation (22)(23)(24)(25). In addition, infertile women with high stigma were less likely to seek treatment and more likely to discontinue treatment even if they sought treatment (26,27).…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, Holubova et al (33) demonstrated a direct and significant link between the use of emotion-focused coping strategies and increased internalized stigma in schizophrenia patients. Stigma has been conceptualized by several researchers as a potent stressor that can exacerbate clinical symptoms and potentially trigger illness relapse (34)(35)(36). Consequently, MS patients utilize coping strategies to manage the stress and depression caused by stigma (31).…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 34 Cultural and social factors include the social stigma associated with infertility. 35 , 36 , 37 Unmarried couples in Japan usually do not have children. 38 Further measures that could help improve Japan's current ART and fertility trends can be summarized under the governmental movements to support infertility patients.…”
Section: Discussionmentioning
confidence: 99%